Tổ chức dạy học nội dung “Tách chiết DNA” (Sinh học 12) theo mô hình 5E nhằm phát triển năng lực tìm hiểu thế giới sống cho học sinh - Nguyễn Văn Hồng, Nguyễn Văn Hồng; Nguyễn Thị Ánh Tuyết, Nguyễn Thị Ánh Tuyết (Tạp chí Giáo dục, 2026)
Understanding the living world is one of the components of biological competence that needs to be formed and developed in students during high school biology lessons. Teaching according to the 5E model, with its five stages, offers opportunities to develop various competencies in students. This study applies the 5E teaching process to the teaching of "DNA Extraction" (Biology 12) to develop students' ability to understand the living world. To effectively develop students' ability to understand the living world through the 5E model in biology lessons, teachers need to organize teaching with content appropriate to each stage of the model, linking it to specific manifestations of this competency; simultaneously, the study designs a system of learning activities and assessment tools to monitor the level of development of students' ability to understand the living world.